The Effect of Calcium Carbonate Particle Size and Solubility on the Utilization of Phosphorus from Phytase for Broilers - Manangi, M.K.; Coon, C.N. (International Journal of Poultry Science, 2007)
A twenty-eight day floor pen experiment was carried out using 1680 Cobb-500 male day old chicks to evaluate the impact of feeding different particle sizes of calcium carbonate (CaCO3) on broiler performance and tibia ash. The experiment consisted of 8 treatments with 6 replications per treatment to test 8 different CaCO3 particle sizes. The corn-soybean meal based diets contained 21.5% CP, 3025 kcal ME kg-1, 0.78% Ca, 0.20% Non-phytate P (NPP) with 500 FTU kg-1 of Danisco Phyzyme XP added. The average particle sizes of CaCO3 (along with % solubility) tested were 28 (74.4), 137 (56.4), 299 (47.0), 388 (53.0), 519 (46.7), 760 (45.3), 796 (42.2) and 1306 (43.4) μm. Significantly (p< 0.05) increased weight gains were obtained for chicks fed CaCO3 particle sizes between 137 and 388 μm compared to the gains obtained by feeding either the smallest (28 μm) or largest particle (1306 μm) sizes. An increased mg of ash per tibia was also obtained for the chicks fed CaCO3 particle sizes ranging from 137-388 μm as compared to the smallest (28 μm) or largest particle (1306 μm) sizes. An in vitro phytate P (PP) hydrolysis by a 3-phytase at pH 2.5 and 6.5 using the same 8 different particles sizes of CaCO3 at equivalent to 9 g kg-1 diet was carried out to evaluate the effect of Ca particle size on PP hydrolysis at 15, 30, 60 and 120 min incubation at 37oC. The results indicate a significant (p< 0.05) interaction of Ca particle size and pH on PP hydrolysis with greater effect at pH 6.5. The main effect of particle size showed that the smallest particle size (28 μm) with more solubility (74.4%) had the lowest PP hydrolysis indicating the interference on the action of phytase on PP hydrolysis due to Ca-phytate complex formation. In summary, both in vivo and in vitro studies indicate that a small Ca particle size (28 μm) CaCO3 with a high solubility (>70.0%) limits PP hydrolysis to provide available P for growth and bone ash formation.